158k views
5 votes
What is h(-2)
H(-1.75)
H(1)

What is h(-2) H(-1.75) H(1)-example-1

1 Answer

5 votes


h(x)=\left\{\begin{array}{cccc}-2&amp;if&amp;-2\leq x<-1&amp;(1)\\-1&amp;if&amp;-1\leq x<0&amp;(2)\\0&amp;if&amp;0\leq x<1&amp;(3)\\1&amp;if&amp;1\leq x<2&amp;(4)\end{array}\right\\\\h(-2)\to x=-2\in(1),\ therefore\ h(-2)=-2\\\\h(-1.75)\to x=-1.75\in(1),\ therefore\ h(-1.75)=-2\\\\h(1)\to x=1\in(4),\ therefore\ h(1)=1

User Ege Akpinar
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.